Development of Communication and Speech Skills of Students in the Process of Education - Naviy, Liza; Zhussupbekova, Gulsara G.; Stukalenko, Nina M.; Zhakhina, Bariya B.; Baimanova, Lazzat S.; Kukubaeva, Asiya K. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article aims to study and diagnose school students with disabilities' levels of communication and speech skills development. Communication technologies in the process of forming communicative competence will contribute to the successful implementation of correctional work, if necessary, an individual or adapted educational program for students with disabilities. During the conduction of the study, the authors used the following types of methods: analysis, synthesis, modelling, observation, survey - statistical method analysis of the data allowed to differentiate levels of communication and speech skills development. The authors revealed the most effective forms and methods of work at the literature levels. The scientific-methodical and practical aspects of the application of communication technologies for the development of school students with disabilities' speech activities were generalized. In modern education, it has been substantiated that communication technologies are used as a means of communication skills formation and as a means of activation of the students' cognitive work. Based on the theoretical analysis of the investigated problem and the experimental work results, the authors have formulated the generalizing positions. It was concluded that the solution to the investigation of the school students with disabilities' speech activities development problem is possible at smart scientific and methodological use of communication technologies.